Causes, patterns and severity of androgen excess in 487 consecutively recruited pre- and post-pubertal children. Issue 3 (March 2019) - Idkowiak, Jan; Elhassan, Yasir S; Mannion, Pascoe; Smith, Karen; Webster, Rachel; Saraff, Vrinda; Barrett, Timothy G; Shaw, Nicholas J; Krone, Nils; Dias, Renuka P; Kershaw, Melanie; Kirk, Jeremy M; et al.
Abstract : Objective: Androgen excess in childhood is a common presentation and may signify sinister underlying pathology. Data describing its patterns and severity are scarce, limiting the information available for clinical decision processes. Here, we examined the differential diagnostic value of serum DHEAS, androstenedione (A4) and testosterone in childhood androgen excess. Design: Retrospective review of all children undergoing serum androgen measurement at a single center over 5 years. Methods: Serum A4 and testosterone were measured by tandem mass spectrometry and DHEAS by immunoassay. Patients with at least one increased androgen underwent phenotyping by clinical notes review. Results: In 487 children with simultaneous DHEAS, A4 and testosterone measurements, we identified 199 with androgen excess (140 pre- and 59 post-pubertal). Premature adrenarche (PA) was the most common pre-pubertal diagnosis (61%), characterized by DHEAS excess in 85%, while A4 and testosterone were only increased in 26 and 9% respectively. PCOS was diagnosed in 40% of post-pubertal subjects, presenting equally frequent with isolated excess of DHEAS (29%) or testosterone (25%) or increases in both A4 and testosterone (25%). CAH patients (6%) predominantly had A4 excess (86%); testosterone and DHEAS were increased in 50 and 33% respectively. Concentrations increased above the two-fold upper limit of normal were mostly observed in PA for serum DHEAS (>20-fold in the single case of adrenocortical carcinoma) and in CAH for serum androstenedione. Conclusions: Patterns and severity of childhood androgen excess provide pointers to the underlying diagnosis and can be used to guide further investigations.